KEPEDULIAN PETANI KARET DALAM PENDIDIKAN DAN KESEHATAN KELUARGA DI KENAGARIAN RABI JONGGOR KECAMATAN GUNUNG TULEH KABUPATEN PASAMAN BARAT - Isna, Isna; Bakaruddin, Bakaruddin (STKIP PGRI Sumbar, 2013)
ISNA. (2013). Farmer Awareness Rubber in Education and Health in the Family Kenagarian Rabbi Jonggor District Mountain Tuleh West PasamanÂ This study aims to determine the rubber farmer awareness on education and health in sub-mountain kenagarian rabbi jonggor tuleh West Pasaman. This research is descriptive. Population are smallholder rubber farmers in Rabi kenagarian Jonggor Yag totaled 571KK. Sampel were taken in two ways, the samples were taken by purposive sampling areas (designation) by taking the 3 oblong ellipse Bandar, Tonga and Rabbi Jonggor Huta, arguing the three corner lot people who work as rubber farmers, while the proportion of respondents in a sample taken by 25% of the amount of rubber farmers, so that as many as 50 farmers karet. Hasil population study indicated that: 1) concern for the education of children of rubber farmers in the form of educational facilities including well enough, providing tuition within one month an average of Rp 400,000 - Rp 500.00 and transport classified lancar. Petani rubber tends to get kids to learn on their own and helped belaajar at home. Difficulty in taking care of childrens education is the lack of guide books and 2) health care terhadapap rubber farmers including poor families, because the families are generally treated to a traditional healer, due to the way health care cukcup get tough. The average distance ith home health care is 1-5 km. Is a disease that often affects malaria but berobatnya kedudkun. Medical expenses from the proceeds sendir, but most small rubber farmers get help in the form of a health card. The advantage of free treatment is cost-saving.